The CPO's returns and multi-events in Indonesia - Perlita Sari Rette; Leony Tipaka; Vania Sinambela; Stien Manggopa (Yayasan Widyantara Nawasena Raharja, 2023)
During the period from January 2022 to June 2022, several events in Indonesia tend to have an impact on the palm oil business. This study aims to examine the relationship between CPO's return and market return with 24 firms as the sample. The findings show that the relationship between the returns of CPO's stocks and market returns is weak and unidirectional. It is also found that the systematic risk and return of CPO's stocks tend to be similar between event periods The findings also imply that the events do not result in a significant difference in returns and systematic risk.